Empirical Investigation of the Influence of Fiscal Policy on Sri Lankas Economic Growth from 1990 to 2019 - Maheswaranathan, S; Jeewanthi, K M N (Asian Journal of Economic Modelling, 2021)
Fiscal policy is a macroeconomic instrument used by the government to steady the economy by instigating its revenue such as tax, foreign aid, trade surplus and expenditures. This study explores the impact of Fiscal Policy on the Economic Growth of Sri Lanka using the autoregressive distributed lag (ARDL) approach of cointegration by applying time-series data from 1990 to 2019. The findings of the study revealed that both in the long run and in the short run, fiscal policy has a significant impact on the Economic growth of the country. The value of the long-run coefficient indicates the relationship between fiscal policy and economic growth is stronger. Diagnostic tests such as serial correlation, functional form, normality of error term and heteroscedasticity and CUSUM stability tests are performed to check the heftiness of the ARDL model. To promote the economic growth of the country the government should be pursued an expansionary fiscal policy.